On Working Memory Capacity and Implicit Associations between Advanced Age and Dangerous Driving Stereotypes. Issue 3 (29th January 2013) - Lambert, Ann E.; Seegmiller, Janelle K.; Stefanucci, Jeanine K.; Watson, Jason M.
Summary: Despite a large literature on implicit stereotypes, no one has scientifically documented the stereotype that older adults are dangerous drivers, even though its existence may impact older adults' driving performance through stereotype threat. The present studies are the first to use implicit tests to document the stereotype that older adult drivers are dangerous drivers. Experiment 1 (N = 159) documented a negative stereotype of older adult drivers in young and older adults by using a novel driving and age Implicit Association Test (IAT). Experiment 2 (N = 216) demonstrated that individual differences in working memory capacity moderate the degree to which young adults can willfully change this IAT score such that higher working memory capacity was associated with greater control of this negative stereotype of age and driving. This finding illustrates the potential utility of working memory capacity in interventions designed to reduce the impact of implicit stereotypes and negative attitudes. Copyright © 2013 John Wiley & Sons, Ltd.